Increasing Students' Sense of Nationalims Through Listening to Indonesia Raya Songs in PKN Learning at Kampung Bharu Malaysia Guidance Studio - Zuhra, Naila; Sari, Suci Perwita; Kaman, Supardi Yoga (At- Ta'lim : Jurnal Pendidikan, 2025)
This research aims to increase students' sense of nationalism through listening to the Indonesia Raya Song in PKN learning at the Kampung Bharu Guidance Studio, Malaysia. The research method used is classroom action research (PTK) with a qualitative approach, involving 20 students as research subjects. This research was carried out in several cycles with stages of planning, implementation, observation, and reflection. The results of the study showed that listening to the Indonesia Raya song on a regular basis was able to increase students' understanding, emotional involvement, and nationalism attitudes. Before the study, only 23% of students felt proud to be part of the Indonesian nation, but this figure increased to 85% after the activity was carried out. The use of national anthem media creates a meaningful, interesting, and effective learning experience, especially in instilling the values of the nation's character. The conclusion of this study is that song-based methods can be an effective learning strategy in teaching nationalism, both in the context of students abroad and domestically. This research contributes to the development of PKN teaching methods that are relevant to the challenges of globalization.